In vitro Evaluation of the Calcification Inhibitory Properties of Policosanol, Genistein, and Vitamin D (Reduplaxin®) either Alone or in Combination - Carla Iacobini; Valeria Fassino; Sandro Mazzaferro; Lida Tartaglione (Karger Publishers, 2024)
Introduction: The process of vascular calcification has severe clinical consequences in a number of diseases, including diabetes, atherosclerosis, and end-stage renal disease. In the present study, we investigated the effect of policosanol (Poli), genistein (Gen), and vitamin D (VitD) separately and in association to evaluate the possible synergistic action on inorganic phosphate (Pi)-induced calcification of vascular smooth muscle cells (VSMCs). Methods: Primary human VSMCs were cultured with either growth medium or growth medium supplemented with calcium and phosphorus (calcification medium) in combination with Poli, Gen, and VitD. Alizarin Red staining, mineralization, and the protein expression of RUNX2 and superoxide dismutase-2 (SOD2) were investigated. Results: All three substances tested were effective at reducing osteogenic differentiation of VSMCs in a dose-dependent manner. Poli+Gen, Poli+VitD, Gen+VitD treatment induced a greater inhibition of calcification and RUNX2 expression compared to single compounds treatments. Moreover, the association of Poli+Gen+VitD (Reduplaxin®) was more effective at inhibiting VSMCs mineralization and preventing the increase in RUNX2 expression induced by calcification medium but not modified SOD2 expression. Conclusions: The association of Pol, Gen, and VitD (Reduplaxin®) has an additive inhibitory effect on the calcification process of VSMCs induced in vitro by a pro-calcifying medium.